2013 IEEE 56th International Midwest Symposium on Circuits and Systems (MWSCAS) 2013
DOI: 10.1109/mwscas.2013.6674893
|View full text |Cite
|
Sign up to set email alerts
|

Development of effective information-hiding method for embedded systems

Abstract: This paper reports on the JPEG compression tolerance of novel proposed digital watermarking algorithm that uses the morphological wavelet transform based on max-plus algebra. For objective evaluation, we investigated the image quality and tolerance against graphical data compression attack of an image during the digital-watermarking contest presented by the Committee for Information Hiding and its Criteria (IHC). During benchmarks of this contest, graphical data compression was done to reduce the file size of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…The value of α is chosen by considering the trade-off between image quality and extraction accuracy. On the basis of experiments with several values of α, we have found that 5 is a practical value for α [2], [21].…”
Section: Improved Algorithmmentioning
confidence: 99%
See 1 more Smart Citation
“…The value of α is chosen by considering the trade-off between image quality and extraction accuracy. On the basis of experiments with several values of α, we have found that 5 is a practical value for α [2], [21].…”
Section: Improved Algorithmmentioning
confidence: 99%
“…This is because, in the case of embedding information data in digital contents for mobile applications, real-time processing speed is more important than data security and image quality. With this background, we report max-plus algebra-based morphological wavelet transform (MMT) watermarking as a novel data-embedding algorithm for highly parallel processing with a mobile embedded processor [2], [18], [21]. Figure 18 shows the watermarking flow using the MMT for the case of a 2 × 2 pixel sampling window.…”
Section: Algorithmmentioning
confidence: 99%
“…Consequently, the algorithm for the MMT is assumed to be suitable for embedded low-power processors. Utilizing these features, MMT watermarking has been proposed for mobile embedded devices in our papers [9], [10]. Figure 1 shows the watermarking flow using the MMT for a 2 × 2 pixel sampling window…”
Section: Max-plus Algebra-based Morphological Wavelet Transform Watermentioning
confidence: 99%